A tunable ⵣ‐shaped microstrip leaky wave antenna based on liquid crystal. (13th April 2022) - Al Soad, Odai Hassan Raheem; Fu, Jiahui; Wu, Qun
Summary: This article presents an electrically tunable dual‐beam ⵣ‐shaped microstrip leaky wave antenna (MLWA) based on liquid crystal (LC). A new ⵣ‐shaped microstrip component (Berber's alphabet: pronounced |z|) is proposed as a single unit‐cell to achieve a dual‐beam radiation pattern with adjustable dual‐beam angles controlled by the ⵣ‐shaped length‐to‐width ratio. The dual‐beam radiation pattern of ⵣ‐shaped microstrip is theoretically derived. The tunable dual‐beam scanning is achieved using a nematic liquid crystal (N‐LC). An AC voltage controls the permittivity of N‐LC applied on the inverted radiating metal. The orientation angle of the N‐LC molecules is also determined theoretically. Besides, the MLWA is rearranged due to the meandering configuration of its microstrip transmission lines, which reduces the antenna's size. As a result, this antenna has a symmetrical dual‐beam at a pointing angle of ±37° in the YZ‐plane. Furthermore, the proposed MLWA is tuned up to 25° at a fixed frequency in XZ‐plane directions by applied AC voltage from 0 to 20 V, which changes the permittivity of the N‐LC from 2.47 to 3.25, respectively. Meanwhile, the MLWA has a realized gain of up to 7.5 dB and a beam scanning range of 40° in the XZ‐plane for all operating frequencies. Finally, the proposed antenna can be suitable for satellite and radar communication systems. Abstract : An electrically tunable dual‐beam ⵣ‐shaped microstrip leaky wave antenna (MLWA) based on liquid crystal (LC) is presented. A new ⵣ‐shaped microstrip component (Berber's alphabet: pronounced |z|) is proposed as a single unit‐cell to achieve a dual‐beam radiation pattern. This antenna has a symmetrical dual beam at a pointing angle of ±37° in the YZ‐plane, and it tunes up to 25° at a fixed frequency in XZ‐plane directions.